Scrotal wall metastasis of gastric adenocarcinoma: a rare case report and literature review - Wang, Yuanhao; Hou, Yi; Zhang, Jingyu; Guo, Kunfeng; Luo, Jinyu; Li, Shengnan; Mu, Gang (Frontiers in Oncology, 2025)
Metastasis of gastric adenocarcinoma typically involves the liver, peritoneum, and lymph nodes, whereas scrotal wall metastasis is extremely rare, with very few cases reported in the literature. We report a case of a 60-year-old male patient who presented with right-sided scrotal swelling. The patient had previously undergone total gastrectomy and multiple chemotherapy sessions for gastric adenocarcinoma. In June 2024, the scrotal wall metastasis of gastric adenocarcinoma was confirmed. The patient underwent excision of the right scrotal lesion, spermatic cord excision, and right epididymis and testis resection. Immunohistochemical markers, such as CK20, CK7, and CDX-2, were positive, which supported the diagnosis of metastatic gastric adenocarcinoma. Follow-up three months post-surgery showed no evidence of tumor recurrence.